Peran Pembelajaran Seni Tari dalam Pengembangan Motorik Siswa di SDN Salembaran 3 Tangerang - Nurhaeni, Titin; Kurniawan, Eka Yulyawan; Sumadiningrat, E. (Lembaga Yasin AlSys, 2022)
This study aims to obtain information about how the role of dance learning in the motor development of students at SDN Salembaran 3 and how the results of students' motor development after learning dance. This research was started from February to August 2022. This study used a qualitative approach and a descriptive type of research by taking data at SDN Salembaran 3 with the subject and object of research being class teachers, and students. Data collection techniques were carried out by observation, interviews, questionnaires and documentation. Data analysis was collected by collecting data, reducing data, presenting data, and drawing conclusions. The results showed that students' motor skills can be developed through dance learning. Gross motor skills can be seen from the students' ability to jump, climb, walk and kick the ball. Fine motor skills after carrying out dance learning can be seen from the students' ability to complete tasks that involve fingers. Students can paint, play musical instruments and write. This is supported by the results of students' motor development after learning dance at SDN Salembaran 3 which was obtained through a questionnaire. With a total score of 73.3 and the final average score is 3.66. So if it is converted into qualitative data, it is included in the